Perioperative Complications and Anesthesia Practices in Managing Patients With Quadriplegia Undergoing Surgery: A Systematic Review - Rizk, Abanoub Aziz; Saad, Marina; Singh, Mandeep; Schaller, Bernhard; Venkatraghavan, Lashmi; Chowdhury, Tumul (Frontiers in Medicine, 2022)
Quadriplegia is associated with a multitude of health complications affecting numerous organ systems. Complications during the perioperative periods are not uncommon in this patient population due to abnormal responses to surgical stressors. Such complications include autonomic dysreflexia, cardiac ischemia, and respiratory compromise. Currently, there is no clear consensus on the ideal technique for perioperative anesthesia management in this population. In addition, the relationship between the perioperative complications and anesthesia practices have not been explored in-depth. Therefore, we aimed to investigate perioperative complications in the context of anesthesia that are associated with patients with quadriplegia undergoing various surgical procedures. Our PRISMA compliant systematic review included 12 articles covering the literature from inception to January 12, 2021. The review showed complications being pulmonary, cerebral, but most importantly and commonly cardiac in nature, with many patients suffering hypertension, and many others hypotension. In addition, our review showed that autonomic dysreflexia is common and in majority of patients, it was managed successfully with good recovery. Based on our findings, the use of anesthesia, either general or spinal, can be considered. Future studies are needed to elucidate the exact mechanisms involved in perioperative complications and anesthetic management that are associated with patients with quadriplegia. This review will aid in developing general recommendations based on the information available in the literature to guide perioperative management of this vulnerable patient population.